Constructing national identity through World Heritage: the international and intranational politics of the built environment in Ahmadabad. Issue 2 (1st February 2022) - Janakiraman, Aarthi
ABSTRACT: In 2017, amidst rising Hindu nationalist politics, the 'Historic City of Ahmadabad' was designated India's first UNESCO World Heritage city for its Islamic architectural heritage. How should we understand the emergence of this seeming counter-narrative at a time of rising ethno-nationalism? Ahmadabad's diverging international and intranational heritage narratives are instructive in understanding what motivates national identity constructions inside and outside a nation-state's borders. Using evidence from semi-structured interviews and documents, this paper illustrates how Ahmadabad's World Heritage narrative is manipulated for different objectives at each scale. Internationally, Ahmadabad's heritage cooperation with the French government, and framing as 'multicultural' is intended to internationalise the city and appeal to a global audience. Internally, its framing suggests inclusivity but operates as a subtle form of control by presenting a carefully curated degree of Islamism. Ultimately, this narrative of inclusion excludes the Muslim and migrant populations most closely associated with this heritage. By unpacking the socio-political and economic forces at play in constructing Indian national identity internationally and internally, this paper highlights the uses and abuses of built heritage.